PDCA IN EDUCATIONAL QUALITY CONTROL - Hasnawi; Ismawati; Jamaluddin (Journal Informatic, Education and Management (JIEM), 2026)
PDCA (Plan-Do-Check-Act) is a quality management cycle developed by W. Edwards Deming based on the basic concepts of Walter Shewhart. In the educational context , PDCA is an important instrument to ensure continuous improvement of the quality of educational services . This article analyzes the concept of PDCA, its implementation stages , and practical applications in educational institutions . Through a literature study approach and conceptual analysis , this study shows that the integration of PDCA in the educational quality assurance system can create a systematic , data - based , and adaptive control mechanism to changing stakeholder needs . The implementation of PDCA not only improves the quality of the learning process but also builds a sustainable quality culture in educational institutions .